(untitled) (Boletin Médico de Postgrado, 2024)
Systemic arterial hypertension is a chronic disease causing various cardiovascular complications. Hypertensive patients can be classified according to the circadian pattern of blood pressure by ambulatory blood pressure monitoring. The objective of this research was to determine the findings of respiratory polygraphy and the circadian blood pressure pattern of hypertensive patients who attended the Arterial Hypertension Unit of the Centro Cardiovascular Regional Centro Occidental (ASCARDIO). Patients had an average age of 54 years, 53% were female, with an average BMI of 28.25 kg/m2 and non-smokers (64%); 57% of patients had a diagnosis of OSAHS (41% mild, 29% moderate/severe, respectively). 70% of patients had a minimum oxygen saturation < 85%. The non-dipper pattern was observed equally in patients with moderate and severe OSAHS and was less frequent in patients with mild OSAHS. The dipper pattern was much more frequent in patients with mild OSAHS while the presentation of the Riser pattern was independent of the degree of severity of OSAHS. The extreme dipper pattern was only observed in patients with severe OSAHS.